Investigação sobre a presença de retrotransposons em populações naturais do grupo cardini do gênero Drosophila (Diptera: Drosophilidae) do sul do Brasil - Cordeiro, Juliana (2005)
The cardini group is part of the genus Drosophila and has its geographical distribution in the Neotropics. Some previous studies revealed the high variability in species of this group of flies. Transposable elements are recognized as capable of high potential for generation of genetic variability in the genomes of the organisms where they are present. Considering such assumptions, the present study has the objective to contribute with the molecular, ecological e evolutionary studies of the transposable elements in the cardini group of Drosophila and in the Drosophilidae family, to such, identifying the presence/absence and the patterns of distribution of the retroelements micropia and gypsy in sixteen natural populations of: Drosophila cardinoides (02), D. neocardini (05) and D. polymorpha (09) in the Brazilian States of Santa Catarina and Rio Grande do Sul. Aiming to identify the presence of the retroelement micropia in the genome of these populations, a fragment isolated from the genome of D. hydei was used as probe. We verified that all populations here studied of the cardini group of Drosophila present strong signal of hybridization, indicating that possibly they have sequences very similar to the probe used in their genomes. The analysis of a part of the micropia s reverse transcriptase sequence by the PCR technique shows that almost all the populations have sequences highly similar to the primers used, showing the expected fragment of 812pb. Although the populations of D. polymorpha presented a fragment slightly smaller than those from D. neocardini and D. cardinoides showing differences at the nucleotide level between the sequences. In the analyze of the presence of gypsy element isolated from D. melanogaster s genome, it was observed that all studied populations have DNA sequence homologies with the probe used. Drosophila cardinoides presented six to seven hybridization bands visible in the blots, D. neocardini presented four to five bands and D. polymorpha presented only one or two bands. When the probe used was a part of the env gene of the element gypsy isolated of D. polymorpha, the populations of D. polymorpha present a sole band in the blots, the populations of D. neocardini present three bands, and the populations of D. cardinoides only present very weak bands, but under exposition by a higher time, three to four bands appeared. From all populations of D. neocardini it was obtained bands with very faint signals. When hybridized with this second probe, indicating high nucleotide divergence between the probe isolated from D. polymorpha and the sequences present in the genome of D. neocardini. For all three probes used in this study: gypsy isolated from D. melanogaster, part of the gene env isolated of the element gypsy from D. polymorpha, and the element micropia isolated from D. hydei, we verified the existence of variability in the banding patterns revealed by Southern Blot between the species. For micropia, this variability was verified among the different populations of the same species.